Comparative Study On The Effects of Boiling As Conventional Cooking Method And Microwaving On Bovine Milk Protein - بركات, هلا; الدياب, ديمة; عطيه, رينا (Latakia University Journal -Biological Sciences Series, 2021)
The widespread of microwave oven which is low-powered and faster than conventional methods was accompanied by the increasing importance of studying its effect on nutrients, especially protein. Therefore, the effects of both boiling and microwaving on bovine milk protein in terms of oxidation and hydrolysis were studied.The levels of PCs (an indicator of protein oxidation ) were compared between fresh, conventionally boiled and microwaved milk. Hydrolyzing protein by the acidic method was studied to evaluate the releasing of free amino groups. The heat treatment increased protein oxidation by increasing the levels of PCs. The oxidation rates were lower in the microwaved samples. a decrease in the free amino groups levels was observed in the heat treated samples compared with fresh samples, protein hydrolysis of microwaved samples was greater than conventionally boiled samples which release more free amino groups .